this post was submitted on 18 May 2024
31 points (100.0% liked)
Daily Maths Challenges
208 readers
1 users here now
Share your cool maths problems.
Complete a challenge:
- Post your solution in comments, if it is exactly the same as OP's solution, let us know.
- Have fun.
Post a challenge:
- Doesn't have to be original, as long as it is not a duplicate.
- Challenges not riddles, if the post is longer than 3 paragraphs, reconsider yourself.
- Optionally include solution in comments, let it be clear this is not a homework help forums.
- Tag [unsolved] if you don't have a solution yet.
- Please include images, if your question includes complex symbols, attach a render of the maths.
Feel free to contribute to a series by DMing the OP, or start your own challenge series.
founded 9 months ago
MODERATORS
you are viewing a single comment's thread
view the rest of the comments
view the rest of the comments
solution
Assuming the series converges it converges absolutely. Thereforesum{n/2^(n-1)^ | n >= 1}
= sum{(n+1)/2^n^ | n >= 0}
= sum{n/2^n^ | n >= 0} + sum{1/2^n^ | n >= 0}
= sum{n/2^n^ | n >= 0} + 2
= sum{n/2^n^ | n >= 1} + 2
=>
sum{n/2^(n-1)^ | n >= 1} = sum{n/2^n^ | n >= 1} + 2
=>
2 = sum{n/2^(n-1)^ | n >= 1} - sum{n/2^n^ | n >= 1}
= sum{n/2^(n-1)^ - n/2^n^ | n >= 1}
= sum{n/2^n^ | n >= 1}
= 1/2 * sum{n/2^(n-1)^ | n >= 1}
=>
sum{n/2^(n-1)^ | n >= 1} = 4